Disclosure of Invention
The invention aims to overcome the defects of the prior art, and the first aim is to provide a sodium hyaluronate gel microsphere, the second aim is to provide a preparation method of the sodium hyaluronate gel microsphere, and the third aim is to provide an application of the sodium hyaluronate gel microsphere in preparing a medical filling material.
The above object of the present invention is achieved by the following technical scheme:
the sodium hyaluronate gel microsphere is formed by self-crosslinking hyaluronic acid, a crosslinking bond is an ester bond, the swelling degree of the sodium hyaluronate gel microsphere ranges from 12.5 to 70.9, and the particle size range is 2.8 to 2000 mu m.
The preparation method of the sodium hyaluronate gel microsphere comprises the following steps:
Step S1, dissolving hyaluronic acid or salt thereof and a catalyst in a solvent A to obtain an aqueous phase solution;
s2, dissolving a tackifier in the solvent B to obtain an oil phase solution;
Step S3, mixing the aqueous phase solution and the oil phase solution, and performing suspension polymerization to obtain the aqueous phase solution and the oil phase solution after the reaction is finished;
Wherein:
In the step S1, the catalyst consists of carbodiimide derivatives and N-hydroxysuccinimide derivatives, wherein a group of glucuronic acid and acetamido glucose in hyaluronic acid or salts thereof are recorded as a repeating unit, the mass ratio of the repeating unit in the hyaluronic acid or salts thereof to the substances of the carbodiimide derivatives and the N-hydroxysuccinimide derivatives is 1 (0.3-1.5): 0.15-2.25), the solvent A is one or more selected from water, physiological saline and phosphate buffer solution, the molecular weight of the hyaluronic acid or salts thereof is 40 kDa-1000 kDa, and the concentration of the hyaluronic acid or salts thereof in an aqueous solution is 5-22 wt%;
In the step S2, the tackifier is selected from one or more of cellulose acetate butyrate, cellulose acetate propionate, ethyl cellulose, polymethyl methacrylate, polystyrene and polyvinyl butyral, and the solvent B is selected from organic solvents which are not mutually soluble with water.
Preferably, in step S1, the carbodiimide derivative is selected from one or more of 1-ethyl-3- (3-dimethylaminopropyl) carbodiimide hydrochloride, N ' -dicyclohexylcarbodiimide, N ' -diisopropylcarbodiimide, N-cyclohexyl-N ' - (2-morpholinoethyl) carbodiimide mesylate.
Preferably, in step S1, the N-hydroxysuccinimide derivative is selected from one or more of N-hydroxysuccinimide, N-hydroxysulfosuccinimide sodium salt, N-hydroxysulfosuccinimide.
Preferably, in step S1, the pH of the aqueous solution is in the range of 4.55-6.95.
Preferably, in step S2, the solvent B is selected from one or more of butyl acetate, amyl acetate, hexyl acetate, butyl propionate, butyl butyrate, dimethyl carbonate, diethyl carbonate.
Preferably, in the step S2, the concentration of the tackifier in the oil phase solution is 0.5 to 15wt.%.
Preferably, in the step S3, the volume ratio of the aqueous phase solution to the oil phase solution is 1:1-40.
Preferably, in the step S3, the suspension polymerization temperature is 10-90 ℃, the reaction time is 0.5-24 h, and the stirring rotation speed is 200-1500 rpm.
The sodium hyaluronate gel microsphere or the application of the sodium hyaluronate gel microsphere prepared by any one of the preparation methods in the preparation of medical filling materials.
The beneficial effects are that:
1. the sodium hyaluronate gel microsphere provided by the invention is formed by self-crosslinking of hyaluronic acid, and the carbodiimide derivative or the N-hydroxysuccinimide derivative used for catalyzing the crosslinking reaction is not connected with sodium hyaluronate by chemical bonds after catalysis, so that the sodium hyaluronate gel microsphere can be removed from a product by cleaning, and the adverse reaction risk of a crosslinking agent is reduced;
2. The hyaluronic acid in the sodium hyaluronate gel microsphere provided by the invention is crosslinked through ester bonds, the gel modulus is obviously improved due to the increase of the crosslinking degree, and the degradation period variation range is smaller, so that the sodium hyaluronate gel microsphere can be simultaneously and rapidly degraded, and is particularly suitable for being used as a short-term hard filling material;
3. Compared with the prior art (such as CN 111647193A for obtaining spongy sodium hyaluronate gel), the preparation method provided by the invention can obtain a spherical sodium hyaluronate gel product by a suspension polymerization method, and the spherical sodium hyaluronate gel product has small rolling resistance among spherical particles and is easy to inject.
The generation mechanism of the beneficial effects is as follows:
1. Mechanism for reducing adverse reaction risk of crosslinked product
Carbodiimide derivatives and N-hydroxysuccinimide derivatives are a group of catalysts that can activate carboxyl groups, with glucuronic acid units in HA bearing carboxyl groups, which can be activated. The glucuronic acid and the acetamido glucose both contain hydroxyl groups, and the activated carboxyl groups can react with the hydroxyl groups to form ester bonds, namely, HA and HA are crosslinked, and a crosslinking agent is not required to be additionally introduced. The specific chemical reaction is shown in the following formula (EDC/NHS is taken as an example).
;
The ester bond in the HA crosslinked by the ester bond can be broken by hydrolysis, and the glycosidic bond of glucuronic acid and acetylglucosamine in the HA is not influenced by the ester bond, and can be hydrolyzed (or enzymatically hydrolyzed). The cross-linking agent fragments will not be released after degradation, and therefore there is no cross-linking agent related safety risk. In contrast to the crosslinking agents (such as BDDE) used in the prior art, the crosslinking agents are directly connected with HA molecules during crosslinking to form a chemical bond connecting structure such as HA-BDDE-HA, and the chemical bond connecting structure cannot be removed through cleaning, so that the crosslinking agent molecules are inevitably released after the gel is degraded in a human body, and the risk of adverse reactions related to the crosslinking agents is brought.
2. The mechanism of high modulus and quick degradation is considered
The traditional crosslinking agents BDDE, DVS, lysine and the like crosslink HA gel, wherein the crosslinking bonds are ether bonds and amide bonds, and the chemical bonds have strong hydrolysis resistance. The network pore size of the crosslinked HA gel is small, and the HA enzyme such macromolecular proteins are not allowed to permeate, and the gel can only be degraded from the surface. Therefore, the cross-link hydrolysis and HA enzymolysis paths are considered at the same time, and the enzymolysis paths are the rate-determining steps for the overall degradation of the gel. With the improvement of the crosslinking degree, the enzymolysis resistance of the gel is obviously improved, and the comprehensive degradation time of the gel is obviously improved with the improvement of the crosslinking degree under the in-vivo environment of the simultaneous occurrence of hydrolysis and enzymolysis.
In contrast, the HA gel disclosed in the present invention is crosslinked via an ester bond, which is a readily hydrolyzable chemical bond. The size of the water molecules is smaller than the network pores of the gel, and all chemical bonds in the gel are hydrolyzed simultaneously after the gel is contacted with water. Thus, the hydrolysis pathway is the rate-determining step for the overall degradation of the gel. Even by increasing the degree of crosslinking, the number of ester bonds is increased (while improving the mechanical properties of the gel), since hydrolysis of the ester bonds within the gel occurs simultaneously (water molecules can penetrate the gel network) rather than starting from the surface of the gel particles, the degradation cycle of the gel is less correlated with the degree of crosslinking. Further, the crosslinking degree is improved, the modulus of the gel can be obviously improved, but the degradation time is not obviously increased, and the combination of quick degradation and high modulus of the gel is realized.
3. Mechanism of obtaining spherical sodium hyaluronate gel by suspension polymerization
The rolling resistance among the spherical particles is small and easy to inject, and the irregular particles are in the structures such as bulges and depressions, so that the injection difficulty is high. The disclosed technology (CN 111647193A) is easy to generate porous and foaming structures during the synthesis of block HA gel, and the inventor researches that a small amount of isocyanate (carbodiimide derivative synthesis raw material) is inevitably remained in the production process of the carbodiimide derivative, and carbon dioxide is generated after the isocyanate reacts with water, so that the foaming crosslinked HA is foamed. According to the invention, the aqueous phase solution is dispersed into micron-sized liquid drops, so that carbon dioxide is easy to diffuse and separate from gel, and the crosslinked HA which is compact, round and free of holes can be formed.
Detailed Description
The following describes the essential aspects of the present invention in detail with reference to examples, but those skilled in the art will recognize that the scope of the present invention should not be limited to the specific examples.
1. Preparation of sodium hyaluronate gel microspheres
Example 1:
Step S1, HA (hyaluronic acid, the same applies hereinafter) with molecular weight of 100 kDa is dissolved in deionized water to form a solution with concentration of 10 wt percent. After adjusting pH to 4.8.+ -. 0.05 with 0.1M HCl/NaOH, EDC and NHS were added as a 1-ethyl-3- (3-dimethylaminopropyl) carbodiimide hydrochloride (hereinafter also NHS (N-hydroxysuccinimide, hereinafter also referred to as N-hydroxysuccinimide) =1:0.5:0.5 (molar ratio) to the HA repeating unit (one group of glucuronic acid and acetamido glucose was referred to as one repeating unit), and the mixture was stirred at room temperature to obtain a homogeneous solution as an aqueous phase.
Step S2, dissolving cellulose acetate butyrate in butyl acetate to form a solution with the concentration of 5 wt percent, wherein the solution is used as an oil phase.
And S3, adding 50 mL water phase into 500 mL oil phase under the mechanical stirring of 10 ℃ and 1000 rpm, carrying out suspension polymerization for 24h, centrifuging after the reaction is finished, collecting microspheres, dialyzing sequentially with an oil phase solvent and absolute ethyl alcohol, and drying to obtain the product.
Example 2:
Step S1, dissolving HA with a molecular weight of 200 kDa in deionized water to form a solution with a concentration of 8: 8 wt. After adjusting the pH to 4.8.+ -. 0.05 with 0.1M HCl/NaOH, EDC and NHS were added in a molar ratio of HA repeating unit: EDC: NHS=1:0.5:0.5, and stirred at room temperature to give a homogeneous solution as an aqueous phase.
The other steps were the same as in example 1.
Example 3:
Step S1, dissolving HA with molecular weight of 500 kDa in deionized water to form a solution with concentration of 5 wt%. After adjusting the pH to 4.8.+ -. 0.05 with 0.1M HCl/NaOH, EDC and NHS were added in a molar ratio of HA repeating unit: EDC: NHS=1:0.5:0.5, and stirred at room temperature to give a homogeneous solution as an aqueous phase.
The other steps were the same as in example 1.
Example 4:
Step S1, dissolving HA with molecular weight of 100 kDa in deionized water to form a solution with concentration of 10 wt%. After adjusting the pH to 4.8.+ -. 0.05 with 0.1M HCl/NaOH, EDC and NHS were added in a molar ratio of HA repeating unit: EDC: NHS=1:0.3:0.3, and stirred at room temperature to give a homogeneous solution as an aqueous phase.
The other steps were the same as in example 1.
Example 5:
Step S1, dissolving HA with the molecular weight of 1000 kDa in deionized water to form a solution with the concentration of 5wt percent. After adjusting the pH to 4.8.+ -. 0.05 with 0.1M HCl/NaOH, EDC and NHS were added in a molar ratio of HA repeating unit: EDC: NHS=1:0.5:0.5, and stirred at room temperature to give a homogeneous solution as an aqueous phase.
The other steps were the same as in example 1.
Example 6:
Step S1, dissolving HA with molecular weight of 100 kDa in deionized water to form a solution with concentration of 10 wt%. After adjusting the pH to 4.8.+ -. 0.05 with 0.1M HCl/NaOH, EDC and NHS were added in a molar ratio of HA repeating unit: EDC: NHS=1:1.0:1.0, and stirred at room temperature to give a homogeneous solution as an aqueous phase.
The other steps were the same as in example 1.
Example 7:
Step S1, HA with molecular weight of 100 kDa is dissolved in deionized water to form a solution with concentration of 10 wt percent. After adjusting the pH to 4.8.+ -. 0.05 with 0.1M HCl/NaOH, EDC and NHS were added in a molar ratio of HA repeating unit: EDC: NHS=1:1.5:1.5, and stirred at room temperature to give a homogeneous solution as an aqueous phase.
The other steps were the same as in example 1.
Example 8:
Step S1, HA with molecular weight of 40 kDa is dissolved in physiological saline to form a solution with concentration of 6 wt percent. After adjusting pH to 4.6.+ -. 0.05 with 0.1M HCl/NaOH, DCC and NHS (N, N' -dicyclohexylcarbodiimide) were added as HA repeating units (NHS=1:0.3:0.15) (molar ratio), and the mixture was stirred at room temperature to give a homogeneous solution as a water phase.
Step S2, dissolving cellulose acetate propionate in amyl acetate to form a solution with the concentration of 0.5 wt percent as an oil phase.
And S3, adding 50mL water phase into 50mL oil phase under mechanical stirring at 90 ℃ and 1500 rpm, carrying out suspension polymerization to obtain 0.5h, centrifuging after the reaction is finished, collecting microspheres, dialyzing with an oil phase solvent and absolute ethyl alcohol in sequence, and drying to obtain the product.
Example 9:
Step S1, HA with the molecular weight of 150 kDa is dissolved in normal saline to form a solution with the concentration of 22: 22 wt. After adjusting pH to 6.5.+ -. 0.05 with 0.5M HCl/KOH, DIC (N, N' -diisopropylcarbodiimide, hereinafter also referred to as "Sulfo-NHS") was added as the repeating unit of HA in a molar ratio of DIC to Sulfo-NHS (N-hydroxysulfosuccinimide sodium salt, hereinafter also referred to as "1:1:1.5", and the mixture was stirred at room temperature to give a homogeneous solution as an aqueous phase.
And S2, dissolving polymethyl methacrylate in dimethyl carbonate to form a solution with the concentration of 15 wt percent as an oil phase.
And S3, adding 50mL water phase into 2000 mL oil phase under mechanical stirring at 40 ℃ and 200 rpm, carrying out suspension polymerization for 4h, centrifuging after the reaction is finished, collecting microspheres, dialyzing sequentially with an oil phase solvent and absolute ethyl alcohol, and drying to obtain the product.
Example 10:
Step S1, HA with a molecular weight of 150 kDa is dissolved in phosphate buffer solution to form a solution with a concentration of 5 wt percent. After adjusting pH to 6.9.+ -. 0.05 with 0.5M phosphoric acid/KOH, CMC (N-cyclohexyl-N' - (2-morpholinoethyl) carbodiimide mesylate, hereinafter also NHSS (N-hydroxysulfosuccinimide, hereinafter also) in a molar ratio of 1:1.5:2.25 was added to CMC and NHSS and stirred at room temperature to give a homogeneous solution as aqueous phase.
Step S2, dissolving polyvinyl butyral in butyl butyrate to form a solution with the concentration of 12 wt percent, and taking the solution as an oil phase.
And S3, adding 50 mL water phase into 1000 mL oil phase under the mechanical stirring of 650 rpm at 60 ℃ for suspension polymerization of 2h, centrifuging to collect microspheres after the reaction is finished, dialyzing with oil phase solvent and absolute ethyl alcohol in sequence, and drying to obtain the product.
Comparative example 1 (differing from example 1 in the concentration of HA):
Step S1, dissolving HA with molecular weight of 100 kDa in deionized water to form a solution with concentration of 4: 4 wt%. After adjusting the pH to 4.8.+ -. 0.05 with 0.1M HCl/NaOH, EDC and NHS were added in a molar ratio of HA repeating unit: EDC: NHS=1:0.5:0.5, and stirred at room temperature to give a homogeneous solution as an aqueous phase.
The other steps were the same as in example 1.
Comparative example 2 (differing from example 2 in the concentration of HA):
Step S1, dissolving HA with a molecular weight of 200 kDa in deionized water to form a solution with a concentration of 4: 4 wt. After adjusting the pH to 4.8.+ -. 0.05 with 0.1M HCl/NaOH, EDC and NHS were added in a molar ratio of HA repeating unit: EDC: NHS=1:0.5:0.5, and stirred at room temperature to give a homogeneous solution as an aqueous phase.
The other steps were the same as in example 1.
Comparative example 3 (differing from example 3 in the concentration of HA):
Step S1, dissolving HA with molecular weight of 500 kDa in deionized water to form a solution with concentration of 2 wt%. After adjusting the pH to 4.8.+ -. 0.05 with 0.1M HCl/NaOH, EDC and NHS were added in a molar ratio of HA repeating unit: EDC: NHS=1:0.5:0.5, and stirred at room temperature to give a homogeneous solution as an aqueous phase.
The other steps were the same as in example 1.
Comparative example 4 (differing from example 4 in the ratio of HA repeat units to EDC, NHS):
Step S1, dissolving HA with molecular weight of 100 kDa in deionized water to form a solution with concentration of 10 wt%. After adjusting the pH to 4.8.+ -. 0.05 with 0.1M HCl/NaOH, EDC and NHS were added in a molar ratio of HA repeating unit: EDC: NHS=1:0.2:0.2, and stirred at room temperature to give a homogeneous solution as an aqueous phase.
The other steps were the same as in example 1.
2. Performance testing
1. Microsphere formability
(1) Test sample
The products prepared in examples 1-3 and comparative examples 1-3 of the invention.
(2) Test item
Microcosmic morphology, namely adding physiological saline into a sample to be detected and observing the sample under a microscope.
(3) Test results
As shown in Table 1, not all concentrations of the solutions can be suspension polymerized to give spherical products. As shown in fig. 1 (bottom left) which shows the microscopic morphology of the product of example 1, the product can be seen as fine irregular particles. After reconstitution with physiological saline, the product of example 1 swells into spherical gel particles (on fig. 1). However, the product of comparative example 1 was greatly different from the product of example 1 in terms of morphology before swelling with physiological saline, but it was not maintained in the form of spherical particles after addition of physiological saline, but was directly dissolved in physiological saline to form flocculent floats (lower right in FIG. 1).
;
(4) Analysis of results
The carbodiimide derivative and the N-hydroxysuccinimide derivative form intermediates which are highly reactive in catalyzing the activation of carboxyl groups and can be consumed by hydroxyl groups in water, i.e. the hydroxyl groups in HA and the hydroxyl groups in aqueous solution need to compete for reaction with the activated carboxyl groups in HA. When the concentration of HA in the reaction system is sufficiently low, the number of crosslinks formed by the reaction is insufficient, i.e., the degree of crosslinking is insufficient. Therefore, the gel particles obtained after crosslinking cannot withstand the swelling effect of water molecules and break, and cannot maintain the spherical morphology.
The products obtained in examples 2 to 10 have a similar spheronizability as the product obtained in example 1.
2. Degree of crosslinking and related Properties
(1) Test sample
The products prepared in examples 1, 4, 6, 7 and comparative example 4 of the present invention.
(2) Test item
Swelling degree, namely weighing a sample to be measured, and marking the mass as m1. Adding the product into sufficient physiological saline to fully swell, taking out the swelled gel, wiping free water on the surface, weighing, and marking the mass as m2. The swelling degree was (m 2-m 1)/m 1.
Storage modulus, namely adding a sample to be tested into sufficient physiological saline to fully swell, and removing free water outside the gel microspheres. Gel microspheres were placed on a plate rotor of a rheometer at an experimental temperature of 25 ℃ with a constant strain of 1%, tiled thickness of 1mm, 25mm plate rotor, and the results at 0.1 Hz.
And (3) hydrolyzing, namely adding the sample to be tested into sufficient physiological saline to fully swell, and placing the sample at 70 ℃ to accelerate the hydrolysis. Every 0.5 h observations were made, with no gelatinous particles seen in the solution as hydrolysis endpoint.
And (3) performing enzymolysis, namely taking a 50 mg sample to be detected, and adding 5 mL of 50U/mL of sodium hyaluronate enzyme physiological saline solution. And (3) carrying out enzymolysis at 37 ℃ after uniform oscillation, observing every 1h, and taking gel particles which cannot be observed under a microscope as an enzymolysis end point.
Adding sufficient physiological saline into a sample to be tested for redissolution, sucking the redissolved gel microspheres into a 1 mL syringe, standing, pushing out free water, and setting the pushing speed to be 30mm/min by using a 27G needle.
(3) Test results
As shown in table 2, the properties of the crosslinked HA gel microspheres with different catalyst amounts were significantly characterized.
;
(4) Analysis of results
The crosslinking density and mechanical property are that as the molar ratio of HA repeating units to EDC to NHS is increased from 1:0.3:0.3 (example 4) to 1:1.5:1.5 (example 7), the swelling degree is reduced from 70.9 to 12.5, the storage modulus is increased from 58 Pa to 3.410 Pa (as shown in figure 2), and the promotion is about 59 times, so that the ester bond crosslinking network can realize gradient high-modulus regulation on the premise of no external crosslinking agent. The swelling degree of the products obtained in examples 1 to 10 is in the range of 12.5 to 70.9.
Degradation rate-degree of crosslinking weak coupling-hydrolysis time is prolonged from 4 h to 11 h (less than 3 times), enzymolysis time is prolonged from 5 h to 74 h (about 15 times), and modulus rise amplitude is significantly lower (59 times). The 'weak coupling' phenomenon verifies the core effect of the 'high modulus-fast degradation' of the invention, and the mechanism is that ester bonds are 'easy hydrolysis bonds', water molecules can penetrate through the whole micro-net and break at the same time, but not surface-centripetal layer-by-layer degradation is performed, even if the crosslinking degree is greatly improved, the whole hydrolysis time is still short, and the enzymolysis time is not the step of the whole degradation of the material.
The injectability is that the maximum pushing force of the spheronizable sample is less than or equal to 5N and is far lower than the threshold value of 'comfortable pushing' of a clinically common 27G needle head (about 10N), and the pushing force is not obviously increased along with the increase of the crosslinking degree, so that the round microsphere still keeps the advantage of 'low rolling resistance' under the 'high modulus' state.
The gel formed in comparative example 4 (molar ratio 1:0.2:0.2) has too low a crosslinking density and still has a strong flowability, and the mechanical and degradation properties cannot be tested, further proving that a sufficient crosslinking level is a necessary condition for ensuring spherical gel particles, consistent with the conclusion of "microsphere formability".
3. Infrared spectrum
(1) Test sample
The product obtained in example 7.
(2) Test item
The detection is carried out according to four 0402 infrared spectrophotometry methods in Chinese pharmacopoeia (2020 edition).
(3) Test results
The infrared spectrum of example 7 and the raw materials used therein is shown in FIG. 3.
(4) Analysis of results
Since the infrared characteristics of the products prepared in each example were almost identical, analysis was performed using the representative profile of example 7 (high crosslinking level).
Sodium Hyaluronate (HA) is a polysaccharide whose main infrared characteristic peaks include about 3400 cm -1: O-H stretching vibration (hydroxy group) and about 2900 cm -1: C-H stretching vibration (methylene and methine groups on sugar ring). About 1650 cm -1 and about 1550 cm -1 amide I and amide II bands (from N-acetylglucosamine units). These peaks are observed in both the HA starting material and the gel microspheres. Meanwhile, the infrared peak shape of the HA raw material and the gel microsphere are basically consistent, which indicates that the composition of the gel microsphere is almost HA.
At the same time, however, some of the characteristic peaks of the HA raw material were changed compared to the gel microspheres. For example, about 1600 cm -1 and about 1410 cm -1 (shown as #1 and # 2) the asymmetric and symmetric stretching vibrations of carboxylic acid, the gel microspheres showed a significant decrease in the relative peak intensity, indicating a decrease in the number of carboxyl groups of the gel microspheres relative to the HA starting material, and about 1100-1000 cm -1 (shown as # 3) the C-O-C and C-O stretching vibrations (glycosidic bond and hydroxyl group), the gel microspheres showed a decrease in the relative peak intensity, indicating a decrease in the number of carboxyl groups of the gel microspheres relative to the HA starting material. In addition, the gel microsphere was newly added with a characteristic peak at about 1700 cm -1 (denoted as #4 in the figure) relative to the HA raw material, which was attributed to the stretching vibration peak of the carbonyl group on the ester bond.
The intensity change and the new increase of the infrared peak show that the components of the gel microsphere are still HA. After crosslinking, the amount of carboxyl groups and hydroxyl groups is reduced, and ester bonds are formed.
Taken together, it is shown that gel microspheres are formed by self-crosslinking of ester bonds.
4. Microsphere particle size
(1) Test sample
The products prepared in examples 7 to 10 of the present invention.
(2) Test item
Particle size is determined by adding physiological saline into sample to be measured to reach steady state, and wet-method determination according to the third method (light scattering method) of particle size and particle size distribution determination method of 0982 of pharmacopoeia of the people's republic of China (four parts) (2020 edition).
(3) Test results
Particle size distribution diagrams of the products prepared in examples 7 to 10 are shown in FIG. 4, and particle size statistics are shown in Table 3.
;
(4) Analysis of results
The particle size distribution of the gel microspheres is controlled by parameters such as molecular weight concentration, water-oil ratio and the like, and the microspheres with the size of 2.8-2000 mu m can be prepared. Screening the product can also result in a narrower particle size distribution based on the particle size of the resulting product. The particle sizes of the products obtained in examples 1 to 10 are all in the range of 2.8 to 2000. Mu.m.
It can be seen that, in summary:
1. The sodium hyaluronate gel microsphere provided by the invention is formed by self-crosslinking of hyaluronic acid, and carbodiimide derivatives or N-hydroxysuccinimide derivatives connected with sodium hyaluronate through chemical bonds cannot exist in the product, so that the adverse reaction risk is reduced;
2. The hyaluronic acid in the sodium hyaluronate gel microsphere provided by the invention is crosslinked through ester bonds, the gel modulus is obviously improved due to the increase of the crosslinking degree, and the degradation period variation range is smaller, so that the sodium hyaluronate gel microsphere can be simultaneously and rapidly degraded, and is particularly suitable for being used as a short-term hard filling material;
3. Compared with the prior art (such as CN 111647193A for obtaining spongy sodium hyaluronate gel), the preparation method provided by the invention can obtain a spherical sodium hyaluronate gel product by a suspension polymerization method, and the spherical sodium hyaluronate gel product has small rolling resistance among spherical particles and is easy to inject.
The above-described embodiments serve to describe the substance of the present invention in detail, but those skilled in the art should understand that the scope of the present invention should not be limited to this specific embodiment.